Connecting Structures: resistance, Heroic Masculinity and Anti-Feminism as Bridging Narratives within Group Radicalization - Meiering, David (International journal of conflict and violence, 2020)
This article pursues two objectives. First, it provides a literature review of research on group radicalization and, second, building on previous research about narratives and their influence on radicalization, it introduces a new concept for comparative radicalization studies: bridging narratives. We use this term to address commonalities in the ideological elements found across various radicalized groups. As narratives shape perceptions of the world and guide processes of identification, they assume an important (internal) function in group formation. At the same time, various radical groups (ethnic nationalists, Salafist-jihadists and militant leftists) share core ideological elements, commonalities that can lead to the creation of new coalitions and unexpected alliances (an external function). The common factor among them are constructed conceptions of the adversary – be they modernity, universalism, Jewish people or feminism. Such constructions allow for the fabrication of an enemy as well as specific conceptions of hierarchical social orders. We analyze two examples in this context: anti-feminism (including heroic or toxic masculinity) and the resistance dispositif that promotes vigilante terrorism. This approach allows us to investigate processes of group radicalization while also taking into account their ideological content as well as the formal effects of such content on processes of group-building and the dynamics of radicalization. In the final section, we provide recommendations for action.